A Pragmatic Analysis of English Teachers’ Speech Acts in Language Teaching: A Case Study at Smart Mataram Private Course - Sari, Putu Dewi Novita; Rahman, Arif; Mahsar, Lalu; Arbaiza, Barbara (Journal of Language and Literature Studies, 2025)
Effective classroom communication is a key component in successful language teaching, particularly in EFL contexts where teachers must navigate both linguistic and pedagogical goals. This study investigates the use of speech acts in classroom interactions, with a specific focus on an English teacher at Smart Mataram Private Course. The primary aim was to identify the types, frequency, and pedagogical functions of speech acts employed during instructional activities. Adopting a descriptive qualitative research design, the data were gathered through direct classroom observation, supplemented by audio and video recordings to ensure accuracy and depth of analysis. The collected data were analyzed using Searle’s taxonomy of speech acts, which categorizes language use into five types: directives, representatives, expressives, commissives, and declaratives. The findings revealed that directive speech acts dominated classroom interactions, comprising 43% of all utterances, followed by representatives (30%), expressives (17%), commissives (7%), and declaratives (3%). This distribution highlights the teacher’s reliance on directives for classroom control and instructional delivery, while representatives and expressives played important roles in conveying content and fostering student engagement. The study concludes that speech acts, particularly directives, are central to classroom discourse and serve distinct pedagogical purposes. It also suggests that enhancing teachers’ pragmatic awareness and communicative strategies can improve interactional effectiveness and learning outcomes. These findings have practical implications for teacher training programs, especially in private language institutions, by underlining the importance of speech act competence in supporting interactive and communicative language teaching.